Preparation and Properties of Core-Shell Particles Filled β-Nucleated Polypropylene Random Copolymer Composites. Issue 1 (January 2015) - Li, Youchen; Zhang, Guixin; Fu, Xiaowei; Guo, Weihong
To provide polypropylene random copolymer (PPR) with excellent toughness without lowering its rigidity, a novel kind of core-shell particles (CSP) and β nucleating agent (β-NA) were incorporated into PPR by melt blending. The CSP, in which nano-CaCO3 acted as the core and polyethylene (PE) formed the shell, was also prepared through melt blending. The effects of different proportion of PE shell and nano-CaCO3 core on the properties of β-modified PPR composites were investigated. The dispersion and morphology of CSP were studied by transmission electron microscopy (TEM) and the results showed that the CSP dispersed fairly well in the PPR matrix and the core-shell structure was successfully formed. The nano-CaCO3 core was completely encapsulated by PE, especially at the 50/50 weight ratio. The crystallization behaviour of the PPR composites was characterized by differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WAXD) and polarized optical microscopy (POM). All the results showed that the relative content of β-form crystal was greatly enhanced with the incorporation of β-NA. Furthermore, the weight ratio change of PE/nano-CaCO3 could also increase the relative content of the β-form crystal. Under the combined effects of β-modification and CSP, the mechanical properties of the PPR composites were greatly enhanced without reducing its rigidity.